DETERMINATION OF THE URANIUM CONTENT IN SOME SOIL SAMPLES FROM AJAOKUTA, KOGI STATE: NIGERIA - Arome, Aruwa; Gyuk, Philibus Musa; Ogwo, Achor Mathias; Suleiman, Isah (International Journal of Research -GRANTHAALAYAH, 2019)
This work present the Uranium (238U) content in soil samples collected in Ajaokuta from some villages was been determined. The measurement of the soil Uranium activity concentration were made using a multi–channel pulse height analyzer (Camberra series 10 plus) coupled to a 76.2mm x 76.2mm NaI (TI) scintillation detector. 2.93)The mean Uranium content in the analyzed samples was found to be (44.26 Bq/kg which is higher than the world mean value of 35Bq/kg. The results were in good agreement with others for soils from region which is considered as normal or slightly high in radioactivity level.